AB0598 Does The Presence of Anti-Citrullinated Protein Antibodies Change The Presentation of Systemic Sclerosis?. (15th July 2016) - Laustriat, G.; Degboe, Y.; Ruyssen-Witrand, A.; Constantin, A.; Barnetche, T.; Adoue, D.; Cantagrel, A.
Abstract : Background: Systemic sclerosis (SSc) is one of the most complex and heterogeneous systemic disease. The diagnosis can be helped by the positivity of different characteristic auto-antibodies steered toward topoisomerase I, centromeric protein, RNA polymerase and fibrillarin. Different presentations of the disease can be associated with some specificities of auto-antibodies. Recently, some studies have reported the presence of anti-citrullinated protein antibodies (ACPA) in patients with SSc. Objectives: We have conducted a systematic literature review in order to define the prevalence of ACPA in SSc, and to observe their influence on clinical and paraclinical presentation of the disease. Methods: Literature search was performed in PubMed Medline database on 15 february 2015. Publication were identified through a search that used the terms: ("systemic sclerosis"(MeSH) and "ACPA or anti-CCP or rheumatoid factor or cohort or value diagnostic"). In a first step, we have selected all cohorts over 50 patients with SSc and ACPA identification. In a second step we have included all studies in which the clinical profile of scleroderma was detailed according to their ACPA status. Meta-analyses were performed when there were two or more studies with similar clinical description. Results: For the first question, we identified 13 observational studies merging 1231 patients with SSc. ACPAs were positive for 113 patients, giving a prevalence of ACPA in SSc of 9.2%. In a second step, we identified 9 studies reporting clinical and paraclinical aspects according to their ACPA status. Information was enough to perform a meta-analysis for arthralgia, arthritis, joint erosions, skin sclerosis, pulmonary arterial hypertension, pulmonary fibrosis and gastrooesophageal reflux. We found a significant association between ACPA positivity and the presence of arthritis (OR: 25.48 [11.82–54.47]), joint erosions on X-rays (OR: 13.06 [4.68–36.43]), pulmonary arterial hypertension (OR: 7.72 [2.38 – 25.5]), and pulmonary fibrosis (OR: 2.75 [1, 21–6.24]) (Fig 1 ). Conclusions: ACPA prevalence in scleroderma is 9.2%. Our systematic literature review shows a significant increased risk for erosive arthritis, pulmonary hypertension and pulmonary fibrosis in ACPA positive SSc. ACPA should be systematically included in the check-up of systemic sclerosis. Disclosure of Interest: None declared